1995
DOI: 10.1002/casp.2450050502
|View full text |Cite
|
Sign up to set email alerts
|

Models of responsibility and depression in unemployed young males and females

Abstract: In line with previous research, unemployed youth (n = 94) in Liverpool, Australia, reported significantly more depression and loss of behavioural/emotional control than their employed counterparts (n = 87). There was a significant sex effect on both of these scales, and no sex by employment status interaction. Detailed interviews with the unemployed group provided the basis for assessing the importance of causal vs solution attributions for the mental health of young unemployed people. Brickman et a1.k (1982) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…The worsening of the unemployment situation is worth noting for two reasons. Second, we should note that adolescent unemployment is associated with a wide range of mental health problems (16). Second, we should note that adolescent unemployment is associated with a wide range of mental health problems (16).…”
Section: Severity Of Youth Unemploymentmentioning
confidence: 97%
“…The worsening of the unemployment situation is worth noting for two reasons. Second, we should note that adolescent unemployment is associated with a wide range of mental health problems (16). Second, we should note that adolescent unemployment is associated with a wide range of mental health problems (16).…”
Section: Severity Of Youth Unemploymentmentioning
confidence: 97%
“…self-blame, intrusive thoughts and wishful thinking, have been associated with anxiety/depression, as well as psychosomatic complaints and psychophysiological stress reactions (Brenner et al, 1983(Brenner et al, , 1988Hagströ m, 1988;Turner et al, 1991). However, it has been proposed that self-blame may be related to efforts to become re-employed (Heubeck et al, 1995). As with stress in general, coping with unemployment is influenced by the interaction between a variety of individual (e.g.…”
mentioning
confidence: 93%
“…Evidence of gender differences in personal control orientations appears to be equivocal. While several studies of generalized control orientations have found that women exhibit lower levels of internal control than do men (e.g., Frenkel, 1995), studies of perceived control over specific domains such as physical well-being (Wallhagen, Strawbridge, Kaplan, & Cohen, 1994) and mental health (Heubeck, Tausch, & Mayer, 1995) yielded no significant gender differences in control orientations.…”
Section: Gender and Racial Differences In Personal Controlmentioning
confidence: 97%